The Use of Script Word Card Media to Improve the Reading Ability of Balinese Script Students of TRJ Middle School - Ida Ayu Putu Asti Pratiwi; Maria Osmunda Eawea Monny (Formosa Journal of Multidisciplinary Research, 2023)
The purpose of this study is how is the implementation of the use of script word cards to improve the ability to read Balinese script and what is the impact of using script word cards to improve reading skills in Balinese script? This research uses behavioristic theory and learning strategy theory. This research is a qualitative research, the primary data used is the results of observations, interviews, and questionnaires, the secondary data is obtained from research results, and references. Determination of informants through purposive sampling technique. The data obtained, analyzed, classified, and concluded. The results showed that almost all groups were able to use the script word cards properly and correctly and the impact of using the script word card media showed the ability of the quiz results to average the skill score of 35 students, namely 98 (very capable). The attractiveness of students in participating in learning is 90.5% (good).